The Role of Organizational Communication In Building The Quality of Human Resources Through The Movement To Realize Natural Tourism - Amini, Mega Aisya; J, Juariyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Jember is one of the districts in East Java which has a lot of amazing panoramas and natural charm. One of the natural attractions that is a favorite for tourists is Puger Beach tourism. This research is about the role of organizational communication in building human resource quality through the movement to create natural tourism. The aim of this research is to understand organizational communication in building an HR community, to explain the organizational communication of UPTD TPI Puger in realizing nature tourism in Puger Village, to find out what obstacles the Puger Fisheries Service experiences in building quality human resources. The method used in this research is descriptive qualitative. The sampling technique used purposive sampling and snowball sampling. The data collection method uses interviews. The results of this research show that UPTD TPI Puger built the KUB Minaharja community as a means for communication and discussion to achieve an HR community in the region. The form of communication carried out with the surrounding community is by inviting discussions about the establishment of natural tourism, prospective/traders who will and are already selling in the Puger beach area. Another form of communication is in the form of promotion to the wider community (general) about the potential natural tourism of Puger Beach. The obstacles experienced by the Puger Fisheries Service are the difficulty in gathering residents because they work as fishermen and the large amount of rubbish in the coastal area.